Pengaruh Good Corporate Governance, Cash Holding, Kinerja Keuangan, dan Ukuran Perusahaan terhadap Nilai Perusahaan - Yanti Oktaviana; Eni Wuryani (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to determine the effect of good corporate governance, cash holding, financial performance and company size in firm value. The population in this study were 44 food and baverages companies for the 2019-2022 period listed on the Indonesia Stock Exchange. The independent variables used in the study consist of the board of commissioners (DK). Audit committee (KA), cash holding (CH), company size (LN), financial performance (ROA), while the dependent variable is firm value (PBV). The number of sample uses a quantitative approach. Research data processing using SPSS version 23 with multiple linear regression analysis methods. Based on the result of the analysis that has been carried out, it is foud that the board of commissioners, audit committee, company size has no effect on firm value. While cash holding and ROA have an effect on firm value.